A role for the sodium pump in H2O2-induced vasorelaxation in porcine isolated coronary arteries - Wong, P.S.; Garle, M.J.; Alexander, S.P.H.; Randall, M.D.; Roberts, R.E. (Elsevier, 2014)
Hydrogen peroxide (H2O2) has been proposed to act as a factor for endothelium-derived hyperpolar-ization (EDH) and EDH may act as a ‘back up’ system to compensate the loss of the NO pathway. Here,the mechanism of action of H2O2in porcine isolated coronary arteries (PCAs) was investigated. DistalPCAs were mounted in a wire myograph and pre-contracted with U46619 (1 nM–50 muM), a throm-boxane A2-mimetic or KCl (60 mM). Concentration–response curves to H2O2(1 muM–1 mM), bradykinin(0.01 nM–1 muM), sodium nitroprusside (SNP) (10 nM–10 muM), verapamil (1 nM–10 muM), KCl (0–20 mM)or Ca2+-reintroduction (1 muM–10 mM) were constructed in the presence of various inhibitors. Activityof the Na+/K+-pump was measured through rubidium-uptake using atomic absorption spectropho-tometry. H2O2caused concentration-dependent vasorelaxations with a maximum relaxation (Rmax) of100 ± 16% (mean ± SEM), pEC50= 4.18 ± 0.20 (n = 4) which were significantly inhibited by PEG-catalase at0.1–1.0 mM H2O2(P < 0.05). 10 mM TEA significantly inhibited the relaxation up to 100 muM H2O2(P < 0.05).60 mM K+and 500 nM ouabain significantly inhibited H2O2-induced vasorelaxation producing a relax-ation of 40.8 ± 8.5% (n = 5) and 47.5 ± 8.6% (n = 6) respectively at 1 mM H2O2(P < 0.0001). H2O2-inducedvasorelaxation was unaffected by the removal of endothelium, inhibition of NO, cyclo-oxygenase, gapjunctions, SKCa, IKCa, BKCaKir, KV, KATPor cGMP. 100 muM H2O2had no effects on the KCl-induced vasore-laxation or Ca2+-reintroduction contraction. 1 mM H2O2inhibited both KCl-induced vasorelaxation andrubidium-uptake consistent with inhibition of the Na+/K+-pump activity. We have shown that the vas-cular actions of H2O2are sensitive to ouabain and high concentrations of H2O2are able to modulate theNa+/K+-pump. This may contribute towards its vascular actions.